Beneficial effects of alpha lipoic acid on cerulein-induced experimental acute pancreatitis in rats - DULUNDU, ENDER; ERCAN, FERİHA; ŞENER, GÖKSEL (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2011)
BACKGROUND The present study aimed to determine the effects of alpha lipoic acid (ALA) on blood and tissue biochemical parameters, as well as tissue histopathology, in an experimental rat model of cerulein-induced acute pancreatitis (AP). METHODS Three groups consisting of eight rats each were used, as follows: Group I. controls; Group 2, cerulein-induced pancreatitis group treated with saline; and Group 3, cerulein-induced pancreatitis group treated with ALA. AP was induced by intraperitoneal administration of cerulein (20 mu g/kg) 4 times at I-hour intervals. The animals were decapitated 12 hours after the last dose of cerulein. Blood amylase, lipase, interleukin (IL)-1 beta, and tumor necrosis factor (TNF)-alpha levels, pancreas tissue glutathione (GSH) and malondialdehyde (MDA) levels, as well as myeloperoxidase (MPO) and Na+-K+-ATPase activity were measured. Pancreatic tissue samples were also evaluated histopathologically under a light microscope. RESULTS While plasma amylase, lipase, IL-1 beta, and TNF-alpha levels, and tissue MDA and MPO levels significantly increased in rats with cerulean-induced AP, tissue GSH and Na+-K+-ATPase activity significantly reduced. These changes were reversed and improved with ALA treatment. CONCLUSION Our findings suggest that ALA may significantly reduce morbidity and mortality by preventing organ dysfunction induced by free radicals in the pancreas.
Keywords: Acute pancreatitis; alpha lipoic acid; cerulein; cytokines; free oxygen radicals; ISCHEMIA-REPERFUSION INJURY; NITRIC-OXIDE; LUNG INJURY; PROTECTS; INFLAMMATION; PREVENTION; MODEL